Barbastella barbastellus - Sachanowicz, Konrad; Ciechanowski, Mateusz; Rachwald, Alek; Piskorski, Michał (Zenodo, 2015)
Barbastella barbastellus Pishkash II (41°04.986 ʹ N, 20°31.560 ʹ E, 701 m a.s.l.), 28 September 2005, 4♂ ad., including one that was sexually active, netted while entering a small cave in a limestone gorge. The cave could be used for night-roosting and/or swarming based on what is known from the other Balkan regions (Schunger et al. 2004). The present locality of this species is one of the southernmost on the Balkan Peninsula and demonstrates its wider occurrence in the region, where it has previously been considered to be very local and rare (Paunović et al. 2003). Its nearest previously known localities are in eastern Macedonia (Kryštufek and Petkovski 2003) and central Greece (Hanák et al. 2001). Barbastella barbastellus has been recorded in all of the Balkan countries (Paunović et al. 2003; Pavlinić et al. 2010; Pašić et al. 2013), including Montenegro (A. Rachwald, unpubl. data). Published as part of Sachanowicz, Konrad, Ciechanowski, Mateusz, Rachwald, Alek & Piskorski, Michał, 2015, Overview of bat species reported in Albania with the first country records for eight species, pp. 513-521 in Journal of Natural History 50 on page 515, DOI:10.1080/00222933.2015.1059962, http://zenodo.org/record/3985566